IBDV 3529/92 segment of ORF 2 gene analysis and expression studies in Pichia pastoris - Mohd Shahrin bin Ghazali (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2015)
Infectious Bursal Disease Virus (IBDV) outbreak had been reported to infect broiler chicken in Malaysia and causes high mortality. It had been reported that the virulence and pathogenicity of the virus is related to its coat protein, more specific the VP2 hypervariable regions. The study aimed to determine the mutation occurred in the amino acid sequence which responsible for the outbreak of the disease and increased in the virus virulence. To study this, the nucleotides and protein of the local IBDV isolate was sequenced and analyzed by comparing it with other IBDV that had been reported previously. To obtain the virus sequence, local IBDV isolate strain 3529/92 was propagated in Specific Pathogen Free eggs and RNA was extracted and amplified by RT-PCR before being inserted into pCR2.1 TOPO TA vector for cloning and sequencing. The full length of the gene segment of the coat protein was constructed by concomitantly joining the fragments using the IBDV native restrictions sites in E. coli expression vector, pTrchis2a. The sequence analysis revealed that the local IBDV 3529/92 consists of 3039 nucleotides which encodes for 1012 amino acids. BLAST analysis of the nucleotide sequence showed that the local strain shared the greatest similarities with Dutch D6948 very virulent (vv) IBDV subtypes. Analysis of the VP2 variable regions of 3529/92 showed most of amino acid substitutions occurred at VP2 variable region are very similar to the changes in VP2 variable regions of the vvIBDV subtypes. Phylogenetic analysis showed that 3529/92 isolates belong to the vvIBDV subtype. Recombinant plasmid was constructed and inserted into the yeast expression vector, pPICZ A prior to transformation into Pichia pastoris X33 by electroporation. After the induction of P. pastoris transformant with 0.5% methanol, the production of IBDV polyprotein was observed using Western blot. In P. pastoris, co- or post-translational processing of large polyprotein had occurred generating a stable C-terminal product (VP3).